1989
DOI: 10.1080/01635588909514014
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of papilloma growth in mice fed high‐fat diets during promotion of two‐stage skin carcinogenesis

Abstract: The effect of feeding a high-fat diet during the promotion phase of skin tumorigenesis was assessed in SENCAR mice. Tumors were initiated on the backs of mice by application of 10 nmol 7,12-dimethylbenz[a]anthracene (DMBA); the tumors were then promoted beginning one week later with twice weekly treatments of 2 micrograms 12-O-tetradecanoylphorbol-13-acetate (TPA) each in 0.2 ml acetone. Control diet containing 5% corn oil was fed from four weeks before until one week after DMBA treatment in all groups. A high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
6
1
Order By: Relevance
“…In those investigations we observed that the higher ratios of dietary corn oil to coconut decreased tumor incidence (1,2). Our studies differ from those of other researchers, where the higher amount of fat increased tumor incidence (25). These differences can be attributed to the protocol design.…”
Section: Discussioncontrasting
confidence: 74%
“…In those investigations we observed that the higher ratios of dietary corn oil to coconut decreased tumor incidence (1,2). Our studies differ from those of other researchers, where the higher amount of fat increased tumor incidence (25). These differences can be attributed to the protocol design.…”
Section: Discussioncontrasting
confidence: 74%
“…ob/ob mice lack leptin and are therefore obese. As obesity is linked to increased cancer susceptibility, including skin cancer (6,11,14), it could have disguised the beneficial effect of the lack of leptin in ob/ob mice. We therefore tested whether lipodystrophic ZIP mice (28,29), for which we confirmed both leptin levels below 5% of those in controls (Table 1) and the lack of visible adipose tissue, would be less susceptible to skin carcinogenesis than their normal littermates.…”
Section: Resultsmentioning
confidence: 99%
“…Skin carcinogenesis is enhanced in genetically obese Ay mice (11,14) and in normal mice made obese by feeding a high fat diet (6). Here, we tested the hypothesis that leptin, which is increased in obesity (22)(23)(24)(25) and which has a direct stimulatory effect on skin cells in vivo (39,40) and in vitro (40-42), was responsible for the effects of obesity on the susceptibility to skin carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between DIO and cancer has been shown in multiple tissues and cell types, including breast, colon, pancreas, liver, lung, and leukocytes 10–14 . Studies have been conducted using the two‐stage skin carcinogenesis model to determine the impact of a high‐fat diet on epithelial carcinogenesis 8,15,16 . Administration of an ad libitum high‐fat diet (46% vs. 11% fat) led to significant differences in body weight and more rapid development of skin tumors; however, no differences in the number of tumors were reported between these diet groups 16 .…”
Section: Cr Diet‐induced Obesity and Cancermentioning
confidence: 99%